Identification of QTL underlying the main stem related traits in a doubled haploid barley population - Zhang, Anyong; Zhao, Ting; Hu, Xue; Zhou, Yu; An, Yue; Pei, Haiyi; Sun, Dongfa; Sun, Genlou; Li, Chengdao; Ren, Xifeng (Frontiers in Plant Science, 2022)
Lodging reduces grain yield in cereal crops. The height, diameter and strength of stem are crucial for lodging resistance, stress resistance, photosynthate transport, and grain yield in barley. Understanding the genetic basis of stem benefits barley breeding. Here, we evaluated 13 stem related traits after 28 days of heading in a barley DH population in two consecutive years. Significant phenotypic correlations between stem strength traits and height traits were observed. Using two mapping methods by the experimental data and the BLUP data, we identified 180 QTLs for 13 traits located on chromosomes 1H (3 QTL), 2H (40), 3H (47), 4H (21), 5H (16), 6H (15) and 7H (38). Of them, 22 major and stable QTLs, and 24 QTL clustered regions were identified. Many QTLs were consistent with previously reported traits for grain filling rate, leaf or panicle. These results indicated that stem traits were closely related to yield traits. Furthermore, candidate genes were predicted at these regions of major and stable QTLs, and they were associated with plant development and adverse stress in the transition from vegetative stage to reproductive stage. Collectively, our results provided underlying genetic basis and new information for exploring barley stem morphology, and laid a foundation for further fine mapping and map-based cloning of these QTLs.